The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago - Shamshev, Igor V.; Sinclair, Bradley J.; Khruleva, Olga A. (Zootaxa, 2020)
The empidoid flies of the Russian Arctic islands and Svalbard Archipelago are revised including families Empididae (4 genera, 32 species), Hybotidae (2 genera, 3 species) and Brachystomatidae (1 genus, 2 species). The following ten new species are described: Empididae—Empis septentrionalis Shamshev & Sinclair sp. nov. (Russia: Wrangel Island); Rhamphomyia (Dasyrhamphomyia) gorodkovi Shamshev, Sinclair & Saigusa sp. nov. (Russia: Chukotka mainland, Wrangel Island, Taymyr, Yakutia; USA: Alaska); R. (D.) mallochi Shamshev, Sinclair & Saigusa sp. nov. (Canada: Yukon; Russia: Chukotka mainland, Kolyuchin and Wrangel Islands; USA: Alaska); R. (Pararhamphomyia) subfilicauda Shamshev & Sinclair sp. nov. (Russia: Wrangel Island); R. (P.) submacrura Shamshev & Sinclair sp. nov. (Russia: Wrangel Island); R. (P.) subtenuiterfilata Shamshev & Sinclair sp. nov. (Russia: Wrangel Island, Yakutia); R. (P.) wrangeli Shamshev & Sinclair sp. nov. (Russia: Wrangel Island); R. sublongiseta Shamshev, Sinclair & Saigusa sp. nov. (Canada: Yukon; Russia: Wrangel Island); one species of Rhamphomyia was retained as unnamed due to insufficient material; Hybotidae—Platypalpus septentrionalis Shamshev & Sinclair sp. nov. (Russia: Wrangel Island), P. subtectifrons Shamshev & Sinclair sp. nov. (Canada: Northwest Territories, Yukon; Russia: Wrangel Island; USA: Alaska). For previously described species a short diagnosis and a habitus photo are provided to enable easier recognition. In addition, a key to the species of Rhamphomyia (Empididae) occurring on the Russia Arctic islands and Svalbard Archipelago is compiled. A lectotype is designated for Rhamphomyia armipes Sack, 1923. The male and the female of R. taimyrensis Frey and R. kaninensis Frey are described for the first time, respectively. Tachypeza sericeipalpis Frey is newly recorded from North America (Canada: Northwest Territories, Nunavut) and first illustration of the male terminalia is provided. Trichoclinocera lapponica (Ringdahl) is recorded for the first time from the territory of Russia.